2022
DOI: 10.1002/ajoc.202200455
|View full text |Cite
|
Sign up to set email alerts
|

Coumarin‐based Chemosensors for Metal Ions Detection

Abstract: Coumarins, due to their intense and persistent emission of fluorescence, structural flexibility, and excellent biocompatibility, have become a popular choice in developing new fluorescent chemosensors. Coumarins have long been used for sensing anions, cations, chemically reactive nitrogen, oxygen, sulfur-containing species, and small molecules. They have also been shown to have applicability in imaging, biology, and medical research. Due to the widespread use and excellent biological activity, hundreds of such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 256 publications
0
6
0
Order By: Relevance
“…Coumarin is also a common fluorophore which was used for the construction of different chemosensors for the detection of various metal ions. 66,67 Some research groups combined coumarin with rhodamine to modulate the sensing properties. Cao et al reported a coumarin incorporated rhodamine B derivative (49) (Scheme 7) for sensing of Al 3+ and Ca 2+ in ethanol.…”
Section: Coumarin Incorporated Chemosensorsmentioning
confidence: 99%
“…Coumarin is also a common fluorophore which was used for the construction of different chemosensors for the detection of various metal ions. 66,67 Some research groups combined coumarin with rhodamine to modulate the sensing properties. Cao et al reported a coumarin incorporated rhodamine B derivative (49) (Scheme 7) for sensing of Al 3+ and Ca 2+ in ethanol.…”
Section: Coumarin Incorporated Chemosensorsmentioning
confidence: 99%
“…The wide range of chromophores and fluorophores permits fine-tuning the optical properties exhibited by the final sensor molecule. A successful case is the class of coumarins, which have been used as a fluorescence scaffold for the development of chemosensors for various relevant analytes, the vast majority of which focus on metal ions [ 3 ] ( Figure 1 ). Indeed, metal ionic species are ubiquitous in nature, and many have crucial roles for maintaining the balance of biological systems.…”
Section: Introductionmentioning
confidence: 99%
“…While these methods are very sensitive with a wide range of linearity, still the high cost and long operation, and complicated sampling processes of such techniques increase the need of finding simpler and faster methods that provide similar results in a shorter time. Recently, chemiluminescent sensors were modified to investigate organic and inorganic analytes in biological and environmental systems [28][29][30]. This provides a simple method to detect target molecules/ions with low detection limits over a short time.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, luminescence-based sensors can be further designed to attain a wide range of signaling "antenna" when the analyte covalently binds to the luminescent probe providing opportunities to monitor the concentrations of the target within a short time. This antenna can be observed through changes in the signal's intensities, wavelength, lifetime, and chirality [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation